Molecular characterization, biological activity, and in silico study of 2-(3,4-dimethoxyphenyl)-3-(4-fluorophenyl)-6-methoxy-4H-chromen-4-one as a novel selective COX-2 inhibitor - Rullah, Kamal; Mohd Aluwi, Mohd Fadhlizil Fasihi; M.Yamin, Bohari; Baharuddin, Mohd Syukri; Ismail, Nor Hadiani; YudaTeruna, Hilwan; Abbas Bukhari, Syed Nasir; Jantan, Ibrahim; Jalil, Juriyati; Husain, Khairana; Lam, Kok Wai (Elsevier, 2015)
The present study aimed to characterize and investigate 2-(3,4-dimethoxyphenyl)-3-(4-fluorophenyl)-6-methoxy-4H-chromen-4-one (22) as a novel selective COX-2 inhibitor. The data collected from the single X-ray crystallographic analysis and in silico study provide important insights on the molecular conformation and the binding interactions that are responsible for the COX-2 selectivity.